Exploring the effects of yoga on body composition, fitness, physiology, nutrition, and mental health in adolescents - Sayan Jyoti Bera; Kingshuk Ghosh; Soumyadip Ghosh; Pritee Singha; Atanu Jana; Atish Mukherjee; Indranil Manna (Yoga-Mimamsa, 2025)
Introduction: Adolescents are exposed to various stressors in everyday life. Maintaining health and fitness is essential for the adolescents, who are the future workforce of our country. Yoga may be used to improve health, fitness, and mental well-being. The present study was designed to study the effects of 6 weeks of yoga practice on body composition, physical and physiological variables of adolescent male and female volunteers. Materials and Methods: A total of 140 healthy volunteers (age: 12–16 years) were included, and 20 with a history of illness were excluded; the remaining 120 volunteers were grouped as (a) control group (n = 60) and (b) yoga group (n = 60) and subdivided into (i) male (n = 30) and (ii) female (n = 30) volunteers. The volunteers of the yoga group performed yoga 1 h/d, 6 d/week for 6 weeks, whereas the control group participants did not perform yoga. The socioeconomic status was assessed before the study. Body composition, fitness, physiological variables, nutritional and mental health status were assessed before (0 week) and after (6 weeks) yoga practice. Paired and independent sample t-tests, along with correlation, were performed. Results: Yoga practice increased (p ≤ 0.05) strength, flexibility, anaerobic power, maximum aerobic capacity, forced vital capacity, forced expiratory volume in 1 s, and peak expiratory flow rate and decreased (p ≤ 0.05) resting heart rate, blood pressure, depression, anxiety, and stress scores in both male and female volunteers. Conclusion: Regular yoga practice improves physical and mental health status, which may prevent the risk of cardiorespiratory diseases, obesity, and mental illness.